2017
DOI: 10.1007/s10787-017-0412-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential usefulness of methyl gallate in the treatment of experimental colitis

Abstract: Methyl gallate is a gallotannin widely distributed in nature. Previous studies have demonstrated its antioxidant, anti-inflammatory, antimicrobial and anti-tumor activities. In the present study, the activity of methyl gallate on experimental models of inflammatory bowel disease has been investigated. Experimental colitis was induced in Sprague-Dawley rats through the intracolonic instillation of an acetic acid solution (2 mL, 4% v/v). Methyl gallate (100 and 300 mg/kg, p.o.) and the reference drug mesalazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…As described above, our results showed that gallincin inhibited inflammation and mucosal damage in mouse models. Anzoise et al 12 also observed that gallincin decreased levels of TNF-a, IL-6, and cyclooxygenase 2 in rats with experimental colitis. Another report from Chae et al 11 also showed that gallincin inhibited lipopolysaccharide-induced inflammatory cytokines by suppressing phosphorylation of ERK1/2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As described above, our results showed that gallincin inhibited inflammation and mucosal damage in mouse models. Anzoise et al 12 also observed that gallincin decreased levels of TNF-a, IL-6, and cyclooxygenase 2 in rats with experimental colitis. Another report from Chae et al 11 also showed that gallincin inhibited lipopolysaccharide-induced inflammatory cytokines by suppressing phosphorylation of ERK1/2.…”
Section: Discussionmentioning
confidence: 92%
“…11 In addition, gallincin has spasmolytic, anti-inflammatory, antidiarrheal, and antioxidant actions. 12,13 However, it is still unknown whether intestinal barrier dysfunction can be treated by gallincin. Fortunately, network pharmacology can be used to identify potential mechanisms of traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Based on genome prediction from 16S rRNA gene sequences of microorganisms in anoxic bioreactors inoculated with human fecal samples, predicted functional pathway analysis indicated that at least some Mankai-derived phenolic compounds are metabolized by the human gut microbiota, and thus degraded before human absorption. Although is it widely accepted that plant-derived phenolic compounds, such as protocatechuate, phenylacetate, methylgallate and salicylate have anti-inflammatory, antioxidant, and antitumor properties, and thus have the potential to improve human diseases such as coronary heart diseases, cancer and diabetes [41][42][43][44][45], some plant-derived phenolic compounds, such as catechol and methylcatechol, can have cytotoxic and cancerogenic activities in the human body [46,47]. However, intracerebroventricular 4-methylcatechol has the potential to increase spatial learning and memory and produce an antidepressant effect [48].…”
Section: Discussionmentioning
confidence: 99%
“…It was described that MG attenuates osteoclastic differentiation in vitro and reduces the bone loss induced by lipopolysaccharide in mice (Baek et al 2017). MG was also described to reduced the in ammatory process in mice experimental colitis (Anzoise et al 2018). Our group described an anti-in ammatory effect for MG in the zymosan-induced arthritis (Correa et al 2016).…”
Section: Introductionmentioning
confidence: 90%